Fog harvesting from cooling towers using metal mesh: Effects of aerodynamic, deposition, and drainage efficiencies. (November 2020) - Ghosh, Ritwick; Ganguly, Ranjan
Fog harvesting is recognized as an important alternate source of fresh water. Industrial fog can supplement water for industrial requirement. Collection of fog (drift droplets) from cooling tower plumes is a viable mode of industrial fog harvesting. The present study delves deeper into the findings of our earlier pilot investigation, on cooling tower fog harvesting and unravels how the collection efficiency depends on interaction of the mesh with the oncoming flow and the deposited fog droplets. Herein, we quantify the fog collection and explain the rationale of the individual contributions of aerodynamic, deposition, and drainage efficiencies on the overall collection efficiency. The effect of the mesh orientations and the tangential velocity component of the cooling tower plume (arising out of the cooling tower-fan rotation) are considered. Aerodynamic efficiency of the mesh and pressure drop across is estimated through computational fluid dynamic analysis. Also, an analysis of the force interaction between the mesh wires, deposited droplet, and the fog stream is carried out to identify the salient deterring factors like re-entrainment, clogging, and premature dripping of collected water droplets, based on which the regime of collection is mapped. The best collection configuration is found at an inclination of 15° with the vertical, with an overall collection efficiency of about 16%. The best configuration would allow recovery of re-usable fresh water at a nominal energy penalty of ∼3.9 kWh/m 3 . Our results offer the design bases for developing full-scale fog harvesting setups for industrial cooling towers.